Sodium magnetic resonance imaging using ultra-short echo time sequences with anisotropic resolution and uniform k-space sampling - Konstandin, Simon; Schad, Lothar R. (Magnetic resonance imaging, 2015)
A method for uniform k-space sampling of 3D ultra-short echo time (UTE) techniques with anisotropic resolution in one direction is introduced to increase signal-to-noise ratio (SNR). State-of-the-art acquisition schemes for sodium MRI with radial (projection reconstruction) and twisting (twisted projection imaging (TPI)) trajectories are investigated regarding SNR efficiency, blurring behavior under T2⁎ decay, and measurement time in case of anisotropic field-of-view and resolution. 3D radial and twisting trajectories are redistributed in k-space for UTE sodium MRI with homogeneous noise distribution and optimal SNR efficiency, if T2⁎ decay can be neglected. Simulations based on Voronoi tessellations and phantom simulations/measurements were performed to calculate SNR efficiency. Point-spread functions were simulated to demonstrate the influence of T2⁎ decay on SNR and resolution. Phantom simulations/measurements and in vivo measurements confirm the SNR gain obtained by simulations based on Voronoi cells. An increase in SNR of up to 21% at an anisotropy factor of 10 could be theoretically achieved by TPI with projection adaption compared to the same sequence but without redistribution of projections in k-space. Sodium MRI with anisotropic resolution and uniform k-space sampling is demonstrated by in vivo measurements of human intervertebral disks and heart at 3 T. The SNR gain can be invested in a measurement time reduction of up to 32%, which is important especially for sodium MRI.
Gesehen am 15.11.2017